Platelet inhibition to target reperfusion injury trial: Rationale and study design. Issue 1 (17th December 2018) - Bulluck, Heerajnarain; Chan, Mervyn H. H.; Bryant, Jennifer A.; Chai, Ping; Chawla, Ashish; Chua, Terrance S.; Chung, Yiu‐Cho; Fei, Gao; Ho, Hee H.; Ho, Andrew F. W.; Hoe, Andrew J.; Imran, Syed S.; et al.
Abstract : Background: In ST‐segment elevation myocardial infarction (STEMI) patients treated with primary percutaneous coronary intervention (PPCI), current oral P2Y12 platelet inhibitors do not provide maximal platelet inhibition at the time of reperfusion. Furthermore, administration of cangrelor prior to reperfusion has been shown in pre‐clinical studies to reduce myocardial infarct (MI) size. Therefore, we hypothesize that cangrelor administered prior to reperfusion in STEMI patients will reduce the incidence of microvascular obstruction (MVO) and limit MI size in STEMI patients treated with PPCI. Methods: The platelet inhibition to target reperfusion injury (PITRI) trial, is a phase 2A, multi‐center, double‐blinded, randomized controlled trial, in which 210 STEMI patients will be randomized to receive either an intravenous (IV) bolus of cangrelor (30 μg/kg) followed by a 120‐minute infusion (4 μg/kg/min) or matching saline placebo, initiated prior to reperfusion (NCT03102723). Results: The study started in October 2017 and the anticipated end date would be July 2020. The primary end‐point will be MI size quantified by cardiovascular magnetic resonance (CMR) on day 3 post‐PPCI. Secondary endpoints will include markers of reperfusion, incidence of MVO, MI size, and adverse left ventricular remodeling at 6 months, and major adverse cardiac and cerebrovascular events. Summary: The aim of the PITRI trial is to assess whether cangrelor administered prior to reperfusion would reduce acute MI size and MVO, as assessed by CMR.